A Measure of the Strength of the Relationship Between the Indigenity and Desirability of Queensland State Schools - Michaelson, Matthew Thomas (The Australian Journal of Indigenous Education, 2006)
Abstract Education Queensland’s Remote Area Incentives Scheme (RAIS) is intended to provide financial and other benefits to teachers who choose to accept employment in undesirable locations in the state. On paper, this scheme claims that remoteness from an urban centre is the foremost measure of a school’s undesirability. However, the percentage of Indigenous students in a school has a strong influence on the assignment of transfer ratings to Queensland state schools. This paper provides the details of a statistical analysis that shows that there is a strong relationship between the Indigenity of a school and its institutionalised perception of undesirability. It also includes a survey of urban schools in southeast Queensland that are categorised as less desirable than surrounding schools in the region primarily because there is a higher percentage of Indigenous students enrolled in those schools.